Microbially induced calcite precipitation using Bacillus velezensis with guar gum - Dikshit, Rashmi; Jain, Animesh; Dey, Arjun; Kumar, Aloke (PLOS ONE, 2020)
Mineral precipitation via microbial activity is a well-known process with applications in various fields. This relevance of microbially induced calcite precipitation (MICP) has pushed researchers to explore various naturally occurring MICP capable bacterial strains. The present study was performed to explore the efficiency of microbially induced calcite precipitation (MICP) via locally isolated bacterial strains and role of guar gum, which is a naturally occurring polymer, on the MICP process. The strains were isolated from local soil and screened for urease activity Further, the urease positive strain was subjected to urea and calcium chloride based medium to investigate the efficacy of isolated strain for microbial induced precipitation. Among screened isolates, the soil bacterium that showed urease positive behaviour and precipitated calcium carbonate was subjected to 16S rRNA gene sequencing. This strain was identified as Bacillus velezensis. Guar gum—a natural polymer, was used as a sole carbon source to enhance the MICP process. It was observed that the isolated strain was able to breakdown the guar gum into simple sugars resulting in two-fold increase in calcium carbonate precipitate. Major bio-chemical activities of isolated strain pertaining to MICP such as ammonium ion concentration, pH profiling, and total reducing sugar with time were explored under four different concentrations of guar gum (0.25%, 0.5%, 0.75% and 1% w/v). Maximum ammonium ion concentration (17.5 μg/ml) and increased pH was observed with 1% guar gum supplementation, which confirms augmented MICP activity of the bacterial strain. Microstructural analysis of microbial precipitation was performed using scanning electron microscopy (SEM) and X-ray diffraction (XRD) techniques, which confirmed the presence of calcium carbonate in different phases. Further, XRD and SEM based studies corroborated that guar gum supplemented media showed significant increase in stable calcite phase as compared to media without guar gum supplementation. Significant diverse group of nitrogenous compounds were observed in guar gum supplemented medium when subjected to Gas Chromatography–Mass spectrometry (GC-MS) profiling.